Analisis Perancangan Usaha Pemanfaatan Limbah Produksi Tempe di UMKM Amanah Sanan Malang - Bagus Kurniawan Mahardika; Yuswono Hadi (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2021)
This research aims to minimize waste and increase revenue by utilizing soybean waste in the form of soybean skins and cooking water to produce Tempeh flour and Nata de soya. The study was conducted at Amanah where approximately 50-60 kg of solid waste and more than 45 liters of liquid waste are generated every day. The waste was collected, analyzed, and processed using a business design analysis method. Data were collected through interviews and observations with the owner of Amanah. The financial aspect of the business plan was evaluated using the payback period (PP), net present value (NPV), and internal rate of return (IRR). The results showed that the business plan had a PP of 2.58 years and was considered feasible with an NPV of $42,321,728.56 and an IRR of 56%, which is higher than the minimum acceptable rate of return (MARR) of 17.1%. This research provides a solid foundation for Amanah to develop the project further in the future. Therefore, this study is expected to be useful for other Tempeh industries that want to minimize waste and increase their revenue through waste utilization.